The analysis of beam using FORTRAN 77 programming / Roshidi Mohd Sani and Zainahar Zainul - Mohd Sani, Roshidi; Zainul, Zainahar (2000)
Proper planning and good management that are practiced in this project is the main core of success. But before that, we need to know clearly the main objectives and the goals. We also have to understand the engineering problems and steps to solve it in a specific time towards the professionalism that is the right quality. This chapter will hopefully give answers to the questions asked. We applied all the knowledge we have learned from this course. We hope that our project to be a good contribution to the society.